2018
DOI: 10.1176/appi.focus.16405
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digital Technology on Psychological Treatments and Their Dissemination

Abstract: The psychological treatment of mental health problems is beginning to undergo a sea-change driven by the widespread availability of digital technology. In this paper we provide an overview of the developments to date and those in the pipeline. We describe the various uses of digital interventions and consider their likely impact on clinical practice, clinical services and the global dissemination of psychological treatments. We note the importance of online clinics, blended treatment, digital assessment and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 53 publications
2
65
0
Order By: Relevance
“…On the other hand, users with social anxiety or agoraphobia, or with conditions associated with shame and stigma such as alcohol and substance misuse disorders or bulimia nervosa, may find it easier to engage with digital interventions compared to face-to-face therapy. 42 A key question identified in the top ten priorities is whether the promise that digital interventions can increase reach and access to treatment for underserved groups is actually realised in practice. This requires health services research to investigate the reach and uptake of digital technology interventions in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, users with social anxiety or agoraphobia, or with conditions associated with shame and stigma such as alcohol and substance misuse disorders or bulimia nervosa, may find it easier to engage with digital interventions compared to face-to-face therapy. 42 A key question identified in the top ten priorities is whether the promise that digital interventions can increase reach and access to treatment for underserved groups is actually realised in practice. This requires health services research to investigate the reach and uptake of digital technology interventions in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Results demonstrate that such interventions can achieve similar outcomes as conventional face‐to‐face delivered therapies . Potential benefits of digital interventions could reduce health costs as less hours of therapists are required, but this largely depends on the design of the intervention . Furthermore, considering the stigma surrounding seeking help for mental health, the digital setting could overcome the barrier of low adherence to mental health treatments and increase its reach to people in need of psychological treatments…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been substantially less empirical testing of mindfulness apps compared to CBT-based apps. 19 Commercial mindfulness apps typically provide meditation guides, rather than full, evidence-based standardised training programmes. For instance, one review of the available 'mindfulness' apps identified more than 700 apps on the iTunes store.…”
Section: Technology In Mindfulness-based Interventionsmentioning
confidence: 99%
“…Each teacher had extensive experience delivering MBSR courses (median number of years teaching MBSR: 11 years, range 3-12). The teachers also reported extensive experience practising mindfulness meditation themselves (median years ÂŒ 17, range [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Participantsmentioning
confidence: 99%